MENUMBUHKAN KESADARAN MASYARAKAT TERHADAP ANAK YATIM DAN PIATU MELALUI PROGRAM SANTUNAN ANAK YATIM - Rahman soesilo; Nirfison Nirfison; Imam Arifin; Sartono Sartono; Purwani Husodo; Abu Naim; Suryo Sulistiyo (Jurnal Abdimas Bina Bangsa, 2023)
Orphans should also receive serious attention, don't get abandoned just because of their family's economic limitations, the community must help them so they can live decently and have a good future. The donation activity for orphans in the form of a school bag, a package of stationery and money in Lemahbang village, Sukorejo sub-district, Pasuruan, East Java aims to help them a little and motivate and give hope to them that they can still get love and a sense of security and better hopes, as well as the purpose of this activity is to foster a caring attitude from the community towards orphans so that they can experience a decent life like other children in general. The implementation of the activity program is carried out in three stages, namely: (1) socialization; (2) coordination; (3) distribution, through the orphan compensation activity program it is hoped that the community can take part and contribute to the welfare of orphans so that they can be independent so that strong bonds of brotherhood will grow